(untitled) (Research, Society and Development, 2021)
All over the world, accidents by venomous animals are important causes of morbidity and mortality. In Brazil, accidents with venomous animals are a public health problem, especially in municipalities in the interior of the country. Accidents caused by venomous animals can be divided based on the etiological agent of the case, and if necessary, they are divided according to the animal’s gender. Thus, through Datasus, statistical data were collected, which highlighted the problem in the municipality of Goianésia, Goiás, about accidents with venomous animals in the years between 2010 and 2017. During this period, SINAN recorded the occurrence of 132 accidents by animals in the municipality of Goianésia, with an average of 16 new cases per year. Regarding gender, ethnicity and age group, there were more cases in males, browns and aged 20 to 39 years, because they are more susceptible and exposed to heavy and manual work. The main animals that cause these accidents are snakes and scorpions. Venomous animals can kill or cause damage to humans. Therefore, the risk of accidents with poisonous animals can be reduced by taking some general and very simple measures for prevention.